Understanding treatment goals and their application in clinical trial design for patients with Alzheimer disease and caregivers - David Gómez-Ulloa; M Chris Runken; Wilton I Rodriguez; Basilio Hernández; Montserrat Chivite; E Anne Davis; Paul Nisbet (BioExcel Publishing Ltd, 2024)
Background: As research continues towards improved treatments for Alzheimer disease (AD), there is growing interest in the views and needs from patients and caregivers on AD treatments. Methods: In this study, we surveyed patients with AD and caregivers to determine the treatment goals that are most important to them. Patients with AD and caregivers were independently recruited in Europe and North America to complete a web-based survey. Eligible participants were ≥18 years old and diagnosed with mild cognitive impairment or mild-to-moderate AD (patient-reported group) or persons involved in the care of patients with AD (caregiver-reported group). A total of 322 patients and 614 caregivers completed the survey. Results: The demographic characteristics of patients in the patient-reported and the caregiver-reported groups were similar. Disease severity of patients was greater in the caregiver-reported group compared with the patient-reported group (72.1% versus 46.9% moderate AD). The most important goal of AD treatment in both groups was maintenance of quality of life (QoL) (patient-reported group 31.1% and caregiver-reported group 38.8%; p=0.01). This was consistent across disease stages or symptom severity except for patients with mild cognitive impairment in the caregiver-reported group where slowing the progression of memory loss was the most important treatment goal. Conclusions: Patient QoL was consistently the most relevant treatment goal for patients with AD and caregivers. In AD clinical trials, patient-relevant outcomes, for example, QoL, should be given high priority to reflect the needs and demands of patients with AD and their caregivers. A preliminary report of this work was presented at the 14th Clinical Trials on Alzheimer's Disease meeting (November 9-12, 2021).